A new selective chromogenic and turn-on fluorogenic probe for copper(ii) in solution and vero cells: recognition of sulphide by [CuL]1. Issue 14 (14th April 2015) - Mahapatra, Ajit Kumar; Mondal, Sanchita; Manna, Saikat Kumar; Maiti, Kalipada; Maji, Rajkishor; Uddin, Md. Raihan; Mandal, Sukhendu; Sarkar, Deblina; Mondal, Tapan Kumar; Maiti, Dilip Kumar
<x xml:space="preserve">Abstract</x> A new coumarin-appended thioimidazole-linked imine conjugate, viz. L has been synthesized and characterized for a selective turn-on fluorescence chemosensor for Cu2+.